EXPERT CONSENSUS ON ETHYL ETHER OF ω-3 POLYUNSATURATED FATTY ACIDS 90% FOR THERAPY AND PREVENTION OF CHRONIC HEART FAILURE EXECUTIVE SUMMARY OF EXPERT COUNCIL, JUNE 2011 (Столичная издательская компания, 2016)
.